Prevalence and characteristics of TERT and TERC mutations in suspected genetic pulmonary fibrosis. Issue 6 (11th November 2016) - Borie, Raphael; Tabèze, Laure; Thabut, Gabriel; Nunes, Hilario; Cottin, Vincent; Marchand-Adam, Sylvain; Prevot, Grégoire; Tazi, Abdellatif; Cadranel, Jacques; Mal, Herve; Wemeau-Stervinou, Lidwine; Bergeron Lafaurie, Anne; et al.
Telomerase reverse transcriptase ( TERT ) or telomerase RNA ( TERC ) gene mutation is a major monogenic cause of pulmonary fibrosis. Sequencing of TERT / TERC genes is proposed to patients with familial pulmonary fibrosis. Little is known about the possible predictors of this mutation and its impact on prognosis. We retrospectively analysed all the genetic diagnoses made between 2007–2014 in patients with pulmonary fibrosis. We evaluated the prevalence of TERT / TERC disease-associated variant (DAV), factors associated with a DAV, and the impact of the DAV on survival. 237 patients with pulmonary fibrosis (153 with familial pulmonary fibrosis, 84 with telomere syndrome features without familial pulmonary fibrosis) were tested for TERT / TERC DAV. DAV was diagnosed in 40 patients (16.8%), including five with non-idiopathic interstitial pneumonia. Prevalence of TERT / TERC DAV did not significantly differ between patients with familial pulmonary fibrosis or with only telomere syndrome features (18.2% versus 16.4%). Young age, red blood cell macrocytosis, and low platelet count were associated with the presence of DAV; the probability of DAV was increased for patients 40–60 years. Transplant-free survival was lower with than without TERT / TERC DAV (4.2 versus 7.2 years; p=0.046). TERT / TERC DAV were associated with specific clinical and biological features and reduced transplant-free survival. Pulmonary fibrosis patients with TERT / TERC disease-associated variants show reduced transplant-free survival http://ow.ly/EmYs304atGl